O cristianismo na pós-modernidade - Lepargneur, Hubert (Revista Eclesiástica Brasileira, 2004)
A pós-modernidade rompe com vários aspectos do estilo clássico, da cultura tradicional no Ocidente, sem ter achado pontos fixos de segurança para ancorar qualquer previsão futurista. Não se trata nestas páginas de elencar as muitas ramificações atuais do Cristianismo, ortodoxo ou não, nem de propor uma lição moralizadora de volta à antiga disciplina e doutrina, ainda que seja oportuno lembrar que o Cristianismo repousa sobre certos dados bíblicos, alguns fundamentais e um tanto esquecidos ou deformados por interpretações desenfreadas. Trata-se de evocar algumas facetas do complexo condicionamento no qual não pode deixar de evoluir o Cristianismo. Tal aparece o contexto de muitos núcleos dinâmicos de revitalização ou adaptação, cuja evocação ultrapassa nosso tema. Abstract: In Post-modernity there is a rupture with various aspects of the classic style and of the traditional culture of the West, but no secure points seem to have been found in which to anchor any prevision of the future. In these pages we do not intend to discuss the many current ramifications of either orthodox or unorthodox Christianity. Neither do we want to propose a moralizing return to the old discipline and doctrine, although it is always opportune to remember that Christianity rests on certain Biblical data, some of which are essential but have been somewhat forgotten or misrepresented by unrestrained interpretations. What we hope to do is to bring to the fore some facets of the complex conditioning in which Christianity must, per force, develop. These emerge in the context of many dynamic nuclei of revitalization or adaptation, the analysis of which goes beyond the scope of this study.